1966
DOI: 10.1021/j100883a055
|View full text |Cite
|
Sign up to set email alerts
|

A Thermodynamic Study of the Vaporization Behavior of the Substoichiometric Plutonium Dioxide Phase1

Abstract: A thermodynamic analysis of the vaporization of the substoichiometric plutonium dioxide phase [~1.6 O/Pu 5$ 2.0] is presented. The results are based on measurements of the vapor pressure of known compositions in tungsten, rhenium, and tantalum effusion cells over the range of temperature 1650 to 2100°K. The vapor pressures are interpretable in terms of Pu02(g), PuO(g), and oxygen as the important vapor species; the partial pressure of the gaseous dioxide is relatively insensitive to the composition of the soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
32
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 5 publications
9
32
2
Order By: Relevance
“…[33][34][35][36][37] for the actinide dioxide series with the newly assessed melting/freezing points of the same compounds. DH sub (298) is in fact known to be much higher for ThO 2 than for the other actinide dioxides (Figure 8), signifying a correspondingly larger cohesion energy of thorium dioxide, which has no f-electrons involved in the formation of molecular orbitals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[33][34][35][36][37] for the actinide dioxide series with the newly assessed melting/freezing points of the same compounds. DH sub (298) is in fact known to be much higher for ThO 2 than for the other actinide dioxides (Figure 8), signifying a correspondingly larger cohesion energy of thorium dioxide, which has no f-electrons involved in the formation of molecular orbitals.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between new and old data points increases with the atomic number of the actinide and the oxygen potential 32 of the corresponding dioxide. Data of the room temperature sublimation enthalpy DH sub (298) [33][34][35][36][37] for the actinide dioxide series are also reported for comparison. Similar to the melting/solidification temperature trend, DH sub (298) is much higher for ThO 2 than for the other actinide dioxides, signifying a correspondingly larger cohesion energy of thorium dioxide, which has no f-electrons involved in the formation of molecular orbitals.…”
Section: Figmentioning
confidence: 99%
“…Also, the decomposition pressure of the Oxides is low [11] even at high temperatures, as is known for substoichiometric dioxides of Pa [16], Pu [17], and Am [18], and for Cm203 [19]. Evaporation of actinide oxides is not a simple process [20].…”
Section: Dioxides and Sesquioxidesmentioning
confidence: 99%
“…Evaporation of actinide oxides is not a simple process [20]. Extensive high-temperature studies were reported for the dioxides of Th [21,22], Pa [16], U [23], Np [24], and Pu [17,18], and for the sesquioxides of Pu [25], Am [20,21], Cm [19,26], Bk [20], Cf [20,27], and Es [20]. Elementary actinides An, the monoxides AnO, and for UO2 and PaOj also AnOj, were observed in the gas phase.…”
Section: Dioxides and Sesquioxidesmentioning
confidence: 99%
“…Pure oxygen gas (mass fraction purity 0.99999) was introduced in the cell and the gas flow was controlled. In order to avoid the direct contact between the solid dioxide sample and the tungsten cell material, because possible reactions at high temperature are suspected [17,18], iridium foils were placed at the bottom of the cells. During the measurements, the temperature was increased at 10 K Á min À1 up to about (2200 to 2300) K for the pure NpO 2 samples.…”
Section: Mass Spectrometric Measurementsmentioning
confidence: 99%